Molecular characterization of Mycobacterium tuberculosis strains resistant to isoniazid - Smaoui, Salma; Siala, Mariem; Hadj Fredj, Sondes; Kammoun, Sana; Marouane, Chema; Hachicha, Salma; Ghorbel, Asma; Gdoura, Radhouane; Slim, Leila; Ben Messaoud, Taieb; Messadi, Férièle (International journal of mycobacteriology, 2016)
Abstract Objective/background Tuberculosis is a major public health problem and the emergence of drug resistance complicates the situation even more. It is therefore crucial to implement all conclusions from the studies that aim at a better understanding of the molecular mechanisms which govern the emergence and the evolution of drug resistance. The aim of this study is to assess the degree of involvement of the inhA and katG genes in the acquisition of isoniazid resistance in clinical strains of Mycobacterium tuberculosis. Methods The inhA and katG genes were sequenced in 21 strains of M. tuberculosis with different resistance profiles and from different regions. Results Analysis of the sequences obtained by comparison to those of the reference strain H37Rv showed that 95.2% had mutations. Kat G S315T was the most common mutation (85.7%). The mutation katG T275A was revealed in two strains (9.5%). Two different point mutations in the inhA gene and its promoter region were identified as C-15T and G56A at a frequency equal to 14% and 10%, respectively. The G56A mutation is a new silent mutation. Our study showed no correlation between found mutations and multidrug resistance. Among the 21 strains studied, only one strain showed no mutations. Conclusion In terms of this study, we characterized the mutations involved in resistance to isoniazid. katG S315T was by far the most frequent mutation, followed by C-15T. The frequency of these mutations was concordant with those reported in literature including those in intermediate tuberculosis endemic countries.